Subjective Temporalities at Play: Temporality, Subjectivity and Gaming Affordances in Cities: Skylines, Europa Universalis IV and Pillars of Eternity. (December 2016) - Gandolfi, Enrico
Background . Despite the increasing attention given by scholars and designers to time as a game variable, an overlooked topic issubjective temporality in play . Aim . This article addresses the issue ofsubjective temporality in play, with a focus on gaming simulations. The purpose of this article is to shed light on how different ludic elements can influence players' diachronic identities. Method . The related concepts ofsameness andselfhood are applied in analyzingCITIES: SKYLINES, EUROPA UNIVERSALIS IV andPILLARS OF ETERNITY . A quantitative survey was distributed online among users of the three case studies (n:387 participants). Instrument items includedplaying habits, sameness andselfhood and thetriggering gaming traits . Results . Specific categories of features are able to fosterselfhood andsameness experiences with various outcomes in terms of the subjects' satisfaction, interpretation and autonomy. Conclusions . Implications of the study are noteworthy for a) practitioners interested in deepening time routines in games through an audiences' lens and b) researchers, who may take inspiration to stress and expand the topic with further focuses and research designs.